Ordinance 21, § 5, in Green Forest Tribune, May 11, 1899, at 1 - (:unkn) unknown (My University, 1899)
Any officer who refuses to make an arrest of someone violating §1-4 shall be fined.
Keywords: PEACE OFFICERS